Breeding of waxy barleys using molecular markers - Vaculova K.; Ehrenbergerova J.; Pouch M. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Low-amylose starch is characteristic of specific physico-chemical properties and in barley (Hordeum vulgare L.) it is connected with high contents of beta-glucans, non-starch polysaccharides with health benefit. A lower proportion of amylose of endosperm starch in grain of initial barley waxy mutants is caused by different expression of granule-bound starch synthase I (GBSS I, E.C. 2.4.1.11) encoded at the Waxy loci. DNA sequence analysis of the insertion/deletion polymorphism, analyzed by PCR reaction at the 5´?leader sequence of the waxy gene, was employed as a molecular marker of the presence of endosperm waxy character in hybrids. Use of various waxy mutants and modern waxy cultivars for hybridization with productive parental partners induced high variability of the yield, vegetative and morphological parameters. The effect of different genetic background on amylose content and other examined agronomic traits of the low-amylose barley lines for food use is discussed.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)